Impact of COVID-19 Pandemic on Young Children With Feeding and Eating Problems and Disorders and Their Families. Issue 4 (15th July 2022) - Krom, Hilde; van Mameren, Joost; Remijn, Lianne; de Nennie, Katinka; Dumont, Eric; van der Gaag, Ellen; van Leeuwen, Marianne C. C.; Mulkens, Sandra; Schakelaar, Chantal; Kindermann, Angelika
Abstract : Objectives: The incidence of feeding and eating problems and disorders (FEPD) in children increased during the coronavirus disease 2019 (COVID-19) pandemic. The aim of this study was to assess the impact of the COVID-19 pandemic on young children with FEPD and their parents. Methods: Cross-sectional survey: parents of children with FEPD (0–11 years) in the Netherlands completed an online questionnaire (January–April 2021). This questionnaire included 4 demographic questions (including criteria of pediatric feeding disorder [PFD] and/or avoidant/restrictive food intake disorder [ARFID]) and 11 questions related to experienced impact of the COVID-19 pandemic. Parental responses regarding children with FEPD (including PFD and ARFID) were compared with those of healthy controls (HCs). Results: In total, 240 children (median age, 5.5 years; interquartile range [IQR], 3.5–7.9 years; 53.3% female) were included; 129 children with FEPD and 111 HC. Most children with FEPD fulfilled criteria for PFD (n = 119; 92.2%) and/or ARFID (n = 117; 90.7%). Parents of children with FEPD reported more stress (of their child [ P = 0.014] and parental stress [ P = 0.014]), worse eating by the child ( P < 0.001), more negative relations within the family ( P = 0.006), and less support from the environment ( P = 0.001) compared with parents of HC during the COVID-19 pandemic than before. Conclusions: It seems that the COVID-19 pandemic had great impact on young children with FEPD and their parents because parents of children with FEPD reported significantly more perceived stress within both the child and parents, more difficult eating behavior of the child, more negative behavior between family members, and less support from the environment as compared with HC.